2014
DOI: 10.1021/jm401665x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Binding Site on Human Choline Kinase α1: Design, Synthesis, Crystallographic Studies, and Biological Evaluation of Asymmetrical Bispyridinium Derivatives

Abstract: Human choline kinase α (CKα) is a validated drug target for the treatment of cancer. In recent years, a large number of CK inhibitors have been synthesized, and one of them is currently being evaluated in Phase I clinical trials as a treatment for solid tumors. Here we have evaluated a new series of asymmetrical biscationic CK inhibitors by means of enzymatic, crystallographic, and antitumor studies. We demonstrate that one of these structures adopts a completely new binding mode not observed before inducing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 26 publications
(62 reference statements)
1
41
0
Order By: Relevance
“…bis-pyridinium, bis-quinolinium) and cytostatic ( e.g. V-11-0711) ChoKα inhibitors may be the length of the molecule and the ability to extend from the choline-binding site to one of the adjacent clefts formed by residues which open or close depending on enzyme conformation [134]. The possibility of undetected off-target binding, however, remains a concern until these discrepancies are resolved.…”
Section: Cancer Cell Death By Chokα Inhibitionmentioning
confidence: 99%
“…bis-pyridinium, bis-quinolinium) and cytostatic ( e.g. V-11-0711) ChoKα inhibitors may be the length of the molecule and the ability to extend from the choline-binding site to one of the adjacent clefts formed by residues which open or close depending on enzyme conformation [134]. The possibility of undetected off-target binding, however, remains a concern until these discrepancies are resolved.…”
Section: Cancer Cell Death By Chokα Inhibitionmentioning
confidence: 99%
“…Combined treatment with 5-fluorouracil and siRNA silencing [30] or Chk-α inhibition [31] demonstrated synergistic effects of both treatments in breast and colorectal cancer models, respectively. Advances have also been made in characterizing the structure of Chk-α through the identification of a new binding site that may result in the design of more effective compounds [32,33]. …”
Section: Molecular Causes and Potential Targets Of Abnormal Choline Metmentioning
confidence: 99%
“…Overall, this compound contains 3 of the 5 moieties present in our proposed pharmacophore (Figure S4) that in turn are required to interact with the protein as described above (Figure 2e and 4a). Owing to these interactions, hit 10 shows two binding modes that allow on one hand to compete with the magnesium atom (this metal is coordinated by Asp330 and Asn311 and the phosphate groups) and the ADP phosphate groups (Figure 4b), and on the other hand to mimic the positive charge present in HC‐3,31 choline/phosphocholine, and HC‐3 derivatives such as compound 12 ,8c compound 13 8b and compound 14 8a (Figures 4b–f). In all these compounds the positive charge is key to maintain a cation‐π interaction with Trp420.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the results of crystallization studies of Hs CKα1 in complex with hit 10, combined with previous structural data,8 contribute to support a scenario in which the majority of Hs CKα1 inhibitors generally occupy the choline‐binding site, using only one positive charged moiety of the molecule to engage aromatic residues in cation‐π interactions. Although the second positive charge of biscationic compounds is usually exposed to the solvent, for one particular compound inducing the aperture of an adjacent new binding site to the choline binding site, it was found that both positive charges are engaged in cation‐π interactions 8a. Remarkably, a second copy of hit 10 has been identified in the ATP binding site, mimicking a magnesium atom that is coordinated by the ATP γ‐phosphate and making electrostatic and hydrogen bond interactions with polar residues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation